1997
DOI: 10.1111/j.1399-6576.1997.tb04616.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous vitamin K1 prior to orthotopic heart transplantation: effects in vivo and in vitro

Abstract: Vitamin K1, administered by intravenous infusion prior to heart transplantation, did not alter subsequent perioperative blood product administration. Vitamin K1 rapidly reversed the anticoagulant effect of warfarin and produced modest hemodynamic changes. The decrease in systemic vascular resistance is probably not due to a direct effect of vitamin K1 on vascular smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…The current dominant management strategy of warfarin cessation, FFP transfusion and vitamin K administration may not be an effective way of reversing warfarin coagulopathy in a medical emergency such as oral anticoagulant therapy-related intracranial haemorrhage. Vitamin K administration entails a small risk of anaphylaxis, may induce modest haemodynamic changes in patients with cardiac dysfunction 10 , which is a common co-existing medical problem in patients on warfarin, and should not be used as monotherapy because it generally takes more than 12 to 24 hours to completely normalise the INR. The use of FFP, at the recommended dose of 15 to 20 ml/kg, implies the infusion of large volumes of plasma, which not only takes several hours to complete, but can also lead to volume overload and heart failure, especially in those with cardiac impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The current dominant management strategy of warfarin cessation, FFP transfusion and vitamin K administration may not be an effective way of reversing warfarin coagulopathy in a medical emergency such as oral anticoagulant therapy-related intracranial haemorrhage. Vitamin K administration entails a small risk of anaphylaxis, may induce modest haemodynamic changes in patients with cardiac dysfunction 10 , which is a common co-existing medical problem in patients on warfarin, and should not be used as monotherapy because it generally takes more than 12 to 24 hours to completely normalise the INR. The use of FFP, at the recommended dose of 15 to 20 ml/kg, implies the infusion of large volumes of plasma, which not only takes several hours to complete, but can also lead to volume overload and heart failure, especially in those with cardiac impairment.…”
Section: Discussionmentioning
confidence: 99%
“…31 Since that report, several in vivo and in vitro studies have been conducted to better elucidate the mechanism behind the cardiovascular effects of vitamin K1. [37][38][39] Barnette et al found that IV vitamin K1-induced hemodynamic changes were consistent with dilation of the arterial system and possibly the venous system through a humoral inflammatory or allergic response. 37 In contrast, Tirapelli et al determined that the dose-dependent decrease in mean arterial pressure seen with IV vitamin K1 most likely involves activation of the nitric oxide pathway and vasodilator release.…”
mentioning
confidence: 99%
“…[37][38][39] Barnette et al found that IV vitamin K1-induced hemodynamic changes were consistent with dilation of the arterial system and possibly the venous system through a humoral inflammatory or allergic response. 37 In contrast, Tirapelli et al determined that the dose-dependent decrease in mean arterial pressure seen with IV vitamin K1 most likely involves activation of the nitric oxide pathway and vasodilator release. 38 Drolet et al reported that IV vitamin K1 exerted a direct effect of on cardiac action potential through blocking major ionic currents, warranting caution in patients sensitive to small changes in action potential (eg, QT interval prolongation [QT] prolongation).…”
mentioning
confidence: 99%